Project-Based Learning Model with Practicum Module Media in The Accounting Information Systems Course at The Economics Diploma Program, University Of Jambi - Gandy Wahyu Maulana Zulma; Lutfi Lutfi; Misni Erwati (Ekonomis: Journal of Economics and Business, 2023)
This research aims to solve the problem of the lack of teaching materials for courses that require special skills such as the Accounting Information Systems course which is one of the mainstay courses in the Diploma 3 Accounting Study Program at the University of Jambi. This research is an exploratory research with a Project-Based Learning approach by developing a practicum module that can be used as a practical tool for vocational students. The population and sample in this study were Diploma 3 Semester 5 students at the Faculty of Economics and Business, Jambi University. This research is expected to produce learning innovation output products that can be used by accounting lecturers to expedite the teaching and learning process such as CPMK (Course Learning Outcomes-Learning Outcomes), Lecture Syllabus and Contracts, Semester Learning Plans (RPS), Student Project Task Plans ( RTM) or student Project Worksheets (LKM) which are expected to be in the form of practicum module books with ISBNs that are published nationally, Learning Outcomes Assessment Sheets (LPHB) according to the project-based learning model or blueprints of exam questions and assessment rubrics which has been reviewed. The results of the study showed that students were able to complete core activities in groups very well. In the assessment of core activities on average, students excel in the aspect of active listening and are slightly weak in completing document reporting. However, overall it can be said that the average rating of each student is in the "Very Good" category. learning achievement reached 86.7% in the "Very Good" category. This means that the project-based learning process through group work in solving problems in the practicum module has proven to be very effective in the Accounting Information Systems course at the D3-Accounting Study Program, Faculty of Economics and Business, University of Jambi.